2017
DOI: 10.1055/s-0042-122818
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of a Self-paced Cardiopulmonary Exercise Test in Post-MI Patients

Abstract: 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 (RPE 11, 13, 15, 17 and 20), following an incremental format. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Furthermore, the difference in absolute between the two protocols was not approaching statistical significance. For evidence of a systematic difference, one would expect a similar statistical difference in both relative and absolute measures of [23,27]. Conspicuously other studies showing an increased relative during PRET max have not reported the accompanying absolute values [1618].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Furthermore, the difference in absolute between the two protocols was not approaching statistical significance. For evidence of a systematic difference, one would expect a similar statistical difference in both relative and absolute measures of [23,27]. Conspicuously other studies showing an increased relative during PRET max have not reported the accompanying absolute values [1618].…”
Section: Discussionmentioning
confidence: 88%
“…Previously Straub et al [20] found CV for of 4% for RAMP and 3% for PRET max , whilst Jenkins et al [27] report values of 4.7% and 8.2% for healthy individuals and cardiac rehabilitation patients, respectively. Corresponding results of 4.8% for RAMP and 4.1% for PRET max in the present study support the reliability of the PRET max .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have serious concerns regarding the safety implications of the study by Jenkins et al [9]. The authors assert that "…the SPV [self-paced peak oxygen uptake test] may be a safe, valid and reliable measure of peak oxygen uptake (VO 2peak ) in both clinical and healthy populations".…”
mentioning
confidence: 99%